The North China lover - Duras, Marguerite (The New Press, 1992)
Hailed in France as "an incomparable pleasure", Marguerite Duras's newest novel is a fascinating retelling of the dramatic experiences of her adolescence that have shaped her work. Far more daring and truthful than any book she has written before, it emphasizes the tough realities of her youth in Indochina and reveals much that her earlier works concealed. An instant number-one bestseller in France, The North China Lover both shocks and entrances its readers. Initially written as notes toward a film script for The Lover, the book has the grainy, filmic qualities of a documentary. Gone are the romantic and nostalgic readings of the past. Here are the humiliations and passions of the poverty-ridden world in which Duras grew up: the intense sexuality of the young women who were her friends and classmates, a group of adolescents impatient for the experiences of adulthood while still caught up in the conflicts of childhood. For all who have admired Duras's previous work, here is an exciting and unexpected reading of her past - a work the French critics called a return to "the Duras of the great books and the great days."